Performance of Village Local Assistance Workers During the Crisis Facing the COVID-19 Pandemic: A Study in Cigandeng Village, Menes District, Pandeglang Regency - Ombi Romli; Siti Nadila Agustina (CV. Lenggogeni Data Publishing, 2023)
This study examines the performance of Village Local Facilitators (PLD) during the Covid-19 crisis in Cigandeng Village, Menes District, Pandeglang Regency. PLDs play a crucial role in supporting village governance as mandated by Law No. 6 of 2014 on Villages, particularly in planning, development implementation, and community empowerment. During the pandemic, PLDs were required to adapt to crisis conditions by conducting socialization of health protocols (5M) and assisting in the management of Village Funds allocated for mitigating the socioeconomic impacts of Covid-19. The research employs a descriptive qualitative method, collecting data through interviews with six informants, including village officials, PLDs, and community representatives. The findings reveal that PLDs generally performed their duties in accordance with governmental regulations, especially in educating the community and facilitating village development during the pandemic. However, there remain challenges in the area of participatory development planning, where the village government still tends to formulate plans independently with limited PLD involvement.